Local vibration influence of electromyography parameters on anaerobic capacity test in rowers - Ciekurs, K.; Krauksts, V.; Krauksta, D.; Grants, J.; Vazne, Ž. (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference. Volume VI, May 22th -23th, 2020, 2020)
Whole body vibration is a worldwide innovation as a part of training method that helps athletes to regain the power and get ready for next training faster. However less attention is paid to local vibration where an isolated muscle or muscle group is stimulated by the use of a vibration device. For the reason to determine the effect of local vibration on anaerobic capacity of rowers, two research groups were assembled from the students of Murjani Sport Gymnasium (MSG). The following methods were used in the study: tests - Concept-2, local vibration (LV) manipulations, electromyography and mathematical statistics. The electromyography was made with Biometric LTD. LV manipulations were done to the muscles erector spinae, latisimus dorsi, teres major, teres minor, trapezius, infraspinatus, deltoideus, slenius capitis, triceps brachii, gluteus maximus, semitendinosus, biceps femoris, semimembranosus, castrocnemius, tendo calcaneus, rectus femoris, vastus lateralis, tensor fascia latae, vastus medialis, sarterius, ligamentum patellae, tibialis anterior, rectus abdominis, pectoralis major un biceps brachii. We using 100 Hz frequency, 2 - 4 mm amplitude and different pressure on the muscles. The total LV application time was 5 to 20 min. The obtained data were processed using mathematical statistics. The results: having stated the result difference before LV and after it. The results testify significant improvement of Concept-2 tests results and electromyography results, what is showed by the difference of the mean results. Comparing the results of the rowers of experimental group (EG) and control group (CG) they have differences in the left side muscle latissimus dorsi after the t-test where p>0.05, but stating the percentage of the mean result difference of this muscle it was found out that p>0.05 what also shows significant changes in the muscle biopotential (mV).